When the War Is Over - Verster, François (Undercurrent Film and Television, 2002)
Duration: 00:52:00 The film deals with the after-effects of the South African struggle against Apartheid, as experienced by survivors from the Bonteheuwel Military Wing (BMW), a militant teenage self-defense unit from the mid-1980s and a guerrilla branch of the ANC. Focusing on two ex-activists, Gori and Marlon, this documentary reveals the scars left among what has become the country’s lost generation. Gori has become an army captain, Marlon a gang member. Both are having trouble finding a path in life: the battle against Apartheid is over, but what now? The documentary is dedicated to seven BMW comrades who were casualties during this time and to the mothers who supported these teenagers during the anti-apartheid struggle. In his straightforward style, director Francois Verster presents an apt, and sometimes frightening, depiction of life in Bonteheuwel.